Direct Power Control of Modular Multilevel Matrix Converter for Flexible Ac Transmission System Applications - Rojas-Lobos, F; Diaz-Diaz, M; Ibaceta-Valenzuela, E; Duran-Sepulveda, A (Institute of Electrical and Electronics Engineers Inc., 2019)
The Modular Multilevel Matrix Converter (M3C) has been proposed as an appropriate alternative for high-power machines due to characteristics such as modularity, medium-voltage operation, high power quality and reliability. However, complex control systems are needed when its ports operate at equal frequencies, and the application of the M3C in equal frequencies applications, such as Flexible AC Transmission System (FACTS), can be restricted. Therefore, this paper presents a direct power control of an M3C for FACTS applications, including an enhanced control system to regulate the floating capacitor voltages, whereas the converter provides functions of FACTS. The effectiveness of the proposed control system is validated through simulations implemented in PLECS software. © 2019 IEEE.